2013
DOI: 10.1007/s00381-013-2103-y
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of navigated intraoperative ultrasonography during resection of fourth ventricular tumors in children

Abstract: Integration of navigated intraoperative ultrasonography in surgery of pediatric fourth ventricular tumors is a useful technology. It safely monitors maximum stepwise tumor excision. It is associated with less operative morbidity without significantly added operative time. It is a real-time, cost-effective, easily applicable, and easily interpretable tool that could substitute the use of intraoperative MRI especially in pediatric neurosurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The expenditure of time for one intraoperative US data set is only 5 minutes [ 30 ]. El Beltagy and Atteya [ 40 ] demonstrate the benefits of intraoperative ultrasound during resection of fourth ventricular tumors in children. They were able to detect and correct tissue shifts at any time during stepwise tumor resection, update new scans, and verify new tumor size by a neuronavigated pointer.…”
Section: Clinical Experience With the State-of-the-art Intraoperatmentioning
confidence: 99%
“…The expenditure of time for one intraoperative US data set is only 5 minutes [ 30 ]. El Beltagy and Atteya [ 40 ] demonstrate the benefits of intraoperative ultrasound during resection of fourth ventricular tumors in children. They were able to detect and correct tissue shifts at any time during stepwise tumor resection, update new scans, and verify new tumor size by a neuronavigated pointer.…”
Section: Clinical Experience With the State-of-the-art Intraoperatmentioning
confidence: 99%
“…Most frequent histology was low-grade glioma (81), followed by medulloblastoma (17), ependymoma (12) and high-grade glioma (10). Additional tumor subtypes included craniopharyngioma (6), germ cell tumors (5), choroid plexus tumors (3) and other less common tumors (20).…”
Section: Resultsmentioning
confidence: 99%
“…The use of iOUS resulted in a 16% increase in GTR achievement (96% vs 80%), while allowing a lower incidence of cerebellar mutism (3% vs 20%) without significant increase of the operative time. They reported ioUS usefulness in detecting residue in the region of the rostral vermis and the lateral recesses of the fourth ventricle (17). No information was provided concerning the patients' randomization process.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the same group reported results for posterior fossa tumors. [19] In this study, they compared navigated US with conventional microsurgery (and navigation) and found that the navigated US group had better GTR rates and lesser mutism postoperatively. Ulrich et al .…”
Section: Discussionmentioning
confidence: 99%